Origin of FDI and domestic productivity spillovers: does European FDI have a 'productivity advantage' in the ENP countries? - Vassilis Monastiriotis (London School of Economics and Political Science (LSE), European Institute, 2014)
The process of approximation between the EU and its 'eastern neighbourhood' has created conditions for deepening economic interactions and market integration, giving to the EU –and to EU businesses– an elevated role in the process of economic modernisation and transition in the neighbourhood countries. This raises the question as to whether European business activity in these countries produces indeed measureable economic advantages both in absolute and in relative terms (e.g., compared to business activity from other parts of the world). Similarly, a question arises as to whether European business activity reduces or amplifies spatial imbalances within the partner countries. This paper examines these issues for the case of capital flows (foreign ownership) and the related productivity spillovers, using firm-level data from the Business Environment and Enterprise Performance Survey (BEEPS) covering 28 transition countries over the period 2002-2009. We estimate the direct and intra-industry productivity effects of foreign ownership and examine how these differ across regional blocks (CEE, SEE and ENP), according to the origin of the foreign investor (EU versus non-EU), across geographical scales (pure industry versus regional spillovers) and for different types of locations (capital-city regions versus the rest). Our results suggest that FDI of EU origin plays a distinctive role in the countries concerned helping raise domestic productivity significantly more than investments from outside the EU. However, this process appears to operate in a spatially selective manner, thus enhancing regional disparities and spatial imbalances. This, then, assigns a particular responsibility for EU policy, as it continues to promote economic integration (and FDI flows) to its eastern neighbourhood, to devise interventions that will help redress these problems.
Keywords: Z00; 330